Experimental Study on Chemical Mechanical Planarization Process by Manufacturing Automated System - Ramlan, S.; Shri Abdul Aziz, M.A.; Md Fauadi, M.H.F.; Muhammad, M.R. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Chemical Mechanical Planarization (CMP) process is one of the critical processes in semiconductor manufacturing. Since in typical semiconductor fab running with high volume and mixed products, good CMP process is required. The process is about planarization. In order to achieve a uniform planar surface, the process control is applied through Integrated Metrology or in this case it is Integrated Thickness Monitoring (ITM) system. ITM simplifies the process control by integrating process and measurement activities in one step. ITM provides feedback on wafer to wafer processing through metrology equipment co-existence in the process equipment. Nevertheless, there is limitation to integrated metrology features, such as recipe matching on individual equipment. In manufacturing facilities, alternative is required to overcome this. Hence, manufacturing automated system capability is extended through Computer Integrated Manufacturing (CIM) system as an alternative to the ITM system, which is called Automated Planarization System (APS). The effectiveness of the alternative system is validated through an experiment. Experiment is done with APS and ITM setup to process similar quantity of wafers. The objective is to observe the process output between the two setups.